2018
DOI: 10.4236/nr.2018.95011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Potential Evaluation of Residues from the Sugarcane Industry of Rio Grande do Sul in Biorefinery Processes

Abstract: Brazil is the world largest producer of sugarcane (Saccharum officinarum) leading to a great generation of residues such as bagasse and straw, which represent two thirds of sugarcane energetic potential. Regarding these residues energetic potential, it is interesting to study their application in biorefinery processes. Thus, this work aimed at performing a chemical characterization of sugarcane straw and bagasse from RB867515 cultivar grown in Rio Grande do Sul-Brazil aiming at their use as feedstock in bioref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…The leaves are also called sugarcane trash and are generally burnt in fields. This produces fly ash and severely damages soil microbial diversity and raises environmental concerns [200,201]. By-products of sugarcane have found application in medicine, pharmaceuticals, confectionary and beverages, electricity, and motor fuels [202].…”
Section: Soybeanmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaves are also called sugarcane trash and are generally burnt in fields. This produces fly ash and severely damages soil microbial diversity and raises environmental concerns [200,201]. By-products of sugarcane have found application in medicine, pharmaceuticals, confectionary and beverages, electricity, and motor fuels [202].…”
Section: Soybeanmentioning
confidence: 99%
“…Machado et al [200] noted that both the bagasse and leaves of sugarcane have potential to be used as substrates to obtain high value-added products from their cellulosic fractions, such as organic acids, biofuels, and biopolymers. Bispo et al [203] produced bio-oil through pyrolysis of sugarcane straw.…”
Section: Soybeanmentioning
confidence: 99%
“…SCB showed higher volatile matter of 58.54% compared to SCBBA and SCBFA with 5.46% and 4.89%, respectively, as these two are by-products from burning of bagasse in the boiler. High volatile matter and fixed carbon for SCB positively influence the biomass calorific value (CV) ( [5,13]). The CV for SCB, SCBBA and SCBFA were 17.…”
Section: Ash Content Calorific Value and Elemental Compositionmentioning
confidence: 99%
“…Data from Companhia Nacional de Abastecimento estimates that, for the 2016/17 harvest, Brazilian sugarcane production was 694.54 million tons, which makes Brazil the world largest producer of sugarcane [1][2]. The solid residue from sugarcane processing represents about 40.11% of dry matter [3], rendering a great opportunity for the waste valorization with the aim of managing waste in the most sustainable way.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…In this scenario, Machado et al [2] observed that sugarcane bagasse has high potential for use as feedstock in biorefineries. Silveira et al [4] utilized the residue as substrate for Monascus purpureus for red pigment production in submerged cultivations.…”
Section: ____________________________________________________________mentioning
confidence: 99%